Fatigue as a key factor for testing knee stability with single leg drop landing for injury prevention and return to play tests - Becker, S.; Simon, S.; Dindorf, C.; Dully, J.; Bartaguiz, E.; Schmitz, L.; Kothe, N.; Fröhlich, M.; Ludwig, O. (Frontiers in Sports and Active Living, 2023)
Objectives Fatigue can decrease knee stability and increase the injury risk. However, fatigue is rarely being applied throughout movement analysis. The aim of this study was to investigate if the knee stability throughout SLDLs differ between cyclic and acyclic sports, before and after fatigue in general, and between the dominant and non-dominant leg of soccer players. Methods A total of 43 active male (n = 34) and female (n = 9) athletes (age: 26.5 ± 7.2) participated in this study with a pre-post-design. Subjects performed a single leg drop landing (SLDL) from a plyobox. For each leg, the two-dimensional frontal plane projection angle (FPPA) was analyzed. After pretesting the shuttle run test was performed until exhaustion, before repeating the measurements. Results ANOVA with repeated measures was applied and identified no significance difference for the FPPA between cyclic and acyclic sports (F = 0.98, p = 0.33), a significant difference before and after fatigue (F = 12.49, p = 0.002) and no significant difference between the dominant and non dominant leg of soccer players (F = 4.35, p = 0.26). Discussion Fatigue seems to be able to have a significant influence on knee stability in the frontal axis. Therefore, fatigue should be included in motion analysis for injury prevention and return to play tests because during this physical state most injuries happen.